Military machines combat vehicles for land, sea & air - Hernandez, Alberto; Valls, Mar; Noden, Jay (Parragon Inc, 2015)
Spanning land, sea and air this military pocket guide book dissects over 60 incredible battle-ready machines from history, using stunning 3-D cut-away illustrations and fact boxes, along with fascinating war scenes that show how this cutting-edge equipment has been so effectively utilized in times of combat. Discover how the astonishing rate of technological advancement has soared throughout the years!!